Clinicomycological Characterization of Superficial Mycoses from a Tertiary Care Hospital in Nepal - Sundar Khadka; Jeevan Bahadur Sherchand; Dinesh Binod Pokharel; Bharat Mani Pokhrel; Shyam Kumar Mishra; Subhash Dhital; Basista Rijal (Dermatology Research and Practice)
Background. Superficial mycosis is a common fungal infection worldwide, mainly caused by dermatophytes. However, the prevalence of species varies geographically. In addition, fungal treatment is best guided according to species isolated. This study was carried out to determine the clinical as well as mycological profile of superficial mycoses in a tertiary care hospital, Nepal. Methods. This was a prospective case-control laboratory based study conducted over a period of six months from January to June 2014 at Tribhuvan University Teaching Hospital, Nepal. A total of 200 specimens were collected from the patients suspected of superficial mycoses. The specimens were macroscopically as well as microscopically examined. The growth was observed up to 4 weeks. Results. Out of total 200 specimens from the patients suspected of superficial mycoses, tinea corporis 50 (25%) was most common clinical types. KOH mount was positive in 89 (44.5%) and culture was positive in 111 (55.5%). Trichophyton mentagrophytes 44 (39.6%) was the most common isolate. Conclusions. The diagnostic yields of KOH mount and culture were found to be complementary to each other. Thus both the methods added with clinical findings are equally important to establish superficial mycosis.